Online English Language Teaching of Grade Eleven Students - Colocado , Ponciano (Journal of Interdisciplinary Perspectives, 2024)
In the Philippines, English teachers face additional challenges with online learning, particularly regarding connectivity issues and the teaching of grammar. Students also struggle with modular distance learning due to the lack of stable social and physical interactions. Considering these challenges, evaluating the effectiveness of online learning in English language teaching can inform decision-making among education stakeholders. Therefore, it is crucial to assess the effectiveness of online learning for Grade 11 English language instruction. To investigate this, the study employed an experimental research design to assess the effectiveness of online English language instruction for Grade 11 students. An equal number of 30 students were allocated to both the control and experimental groups. Specifically, the control group comprised 30 GAS students receiving instruction through the modular approach, while the experimental group consisted of 30 HUMSS students undergoing online English language instruction. A comparative analysis was conducted to ascertain differences between the pretest mean scores of students taught using modular versus online methods, differences between their posttest mean scores under these approaches, and discrepancies between their pretest and posttest mean scores across both approaches. Results revealed that modular and online approaches to teaching English were both effective to the students considering that no significant difference was shown in their pretest mean scores. However, the students were more comfortable with online learning since there was a significant difference in the post-test mean scores when taught using modular and online learning.